Neural correlates of uncertainty processing: meta-analysis of fMRI studies - Timashkov, Andrey; Anderson, Sarah; Zinchenko, Oksana (Frontiers in Neuroscience, 2025)
IntroductionUnderstanding the neural mechanisms underlying decision-making under uncertainty represents a fundamental challenge in cognitive neuroscience. This meta-analysis aimed to identify the consistent neural correlates of uncertainty processing specifically during decision-making tasks.MethodsWe synthesized findings from 76 fMRI studies (N = 4,186 participants). Using the Activation Likelihood Estimation (ALE) method, we performed a voxel-wise meta-analysis of activation foci to identify brain regions consistently activated across studies.ResultsThe analysis revealed nine distinct activation clusters, revealing a comprehensive neural network involved in uncertainty processing. Key findings demonstrated predominant activations in the anterior insula (up to 63.7% representation), inferior frontal gyrus (up to 40.7%), and inferior parietal lobule (up to 78.1%). We found a functional specialization between emotional-motivational processes (clusters 1–5) and cognitive processes (clusters 6–9), with notable hemispheric asymmetries. The left anterior insula was more strongly associated with reward evaluation, while the right was involved in learning and cognitive control. Similarly, the right inferior frontal gyrus was linked to impulse control, and the left to motor planning.DiscussionOur findings extend the current understanding of the neural architecture of decision-making under uncertainty. The comprehensive mapping of neural signatures advances our knowledge of the distinct roles of key brain regions and provides insights into potential clinical applications, particularly for developing interventions for uncertainty-related anxiety. The study highlights important directions for future research in cognitive neuroscience and clinical practice.